Inoculation cored wire for cast iron
By designing a core-shell structure for inoculating alloy powder and an intermetallic compound catalytic layer, the problems of rapid degradation of inoculation effect and low utilization rate in cast iron inoculation cored wires were solved, achieving long-term inoculation and performance stability of castings and improving the quality consistency of castings.
Patent Information
- Application Number
- CN202511034796.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-25
- Publication Date
- 2025-12-05
AI Technical Summary
Existing cast iron inoculation cored wires suffer from problems such as rapid decline in inoculation effect, low utilization rate of effective elements, and poor batch-to-batch stability of product performance.
The inoculating alloy powder adopts a core-shell structure, with a core of highly active barium and calcium and a shell of silicon and rare earth powder. Combined with an intermetallic compound catalytic layer, the catalytic layer is formed on the inner wall of the steel wire carrier through vacuum magnetron sputtering, ensuring the sequential release and efficient utilization of the inoculating elements.
This achieves long-term stability of inoculation effects, improves the utilization rate of inoculants and batch stability of product performance, and ensures the consistency of casting quality.
Smart Images

Figure CN121065430A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of casting materials technology, specifically to a cored wire for cast iron. Background Technology
[0002] In modern machinery manufacturing, gray cast iron plays a crucial role as a basic structural material, from automobile engine blocks to heavy-duty machine tool beds, thanks to its excellent casting performance and cost advantages. The final service performance of these castings, such as strength, wear resistance, and service life, is directly related to their internal microstructure, particularly the morphology, size, and distribution of graphite. Therefore, precisely controlling graphite crystallization through metallurgical methods to obtain uniformly dispersed A-type flake graphite is a core step in improving casting quality. Inoculation treatment, which involves adding specific substances to molten iron to promote favorable nucleation, is an indispensable process for achieving this goal. This invention provides a highly efficient inoculated cored wire for this process.
[0003] In existing technologies, the cored wire feeding method for inoculation has become a mature industrial practice. This technology typically involves wrapping alloy powder containing elements such as silicon, barium, and calcium into a continuous wire using low-carbon steel strip. During application, the cored wire is fed into the molten iron at a controlled speed using specialized equipment. Compared to traditional surface-sprinkled inoculation, this method allows for precise addition of the inoculant, reduces alloy burn-off, and improves the workshop working environment. Its application effectively promotes graphite nucleation in the molten iron, providing a fundamental guarantee for obtaining qualified castings.
[0004] However, existing technologies still reveal several deep-seated shortcomings in practice. First, the commonly used simple mechanical mixing powders contain highly active inoculant components that melt and react instantly upon contact with molten iron, resulting in a concentrated release of the inoculant effect within a very short time, followed by rapid attenuation. Second, traditional steel strip carriers act merely as inert containers during melting, and the molten steel easily encapsulates some of the inoculant powder, hindering its contact with the molten iron and causing low and unstable actual utilization of effective elements. Finally, the active elements in the inoculant inevitably come into contact with air during production and storage, leading to surface oxidation. This slow chemical deterioration reduces the product's effectiveness, resulting in significant differences in performance between different batches or storage times, posing a challenge to the quality consistency control of castings. Therefore, those skilled in the art propose an inoculated cored wire for cast iron to address these problems. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a cored wire for cast iron, which solves the technical problems of rapid degradation of inoculation effect, low utilization rate of effective elements, and poor batch-to-batch stability of product performance in existing technologies.
[0006] To achieve the above objectives, the present invention provides the following technical solution: The first aspect of the present invention provides an inoculated cored wire for cast iron, comprising a steel wire carrier and an inoculated alloy powder filled inside the steel wire carrier.
[0007] The inoculated alloy powder comprises the following components in parts by weight: 65-75 parts silicon powder; 12-18 parts barium powder; 8-12 parts calcium powder; 0.1-1.0 parts rare earth; and the balance being iron and impurities.
[0008] Preferably, the inoculated alloy powder is configured as composite particles with a core and shell structure. This structural design has the following technical advantages: By stratifying components with different melting rates and activities, the inoculum elements can be released sequentially during use. When the cored wire is immersed in molten iron, the outer shell material melts first, providing initial inoculation; subsequently, the inner core material melts again, releasing powerful inoculating elements. This phased mechanism of action prolongs the overall effective time of incubation, thereby inhibiting incubation decline. Preferably, the steel wire carrier has an inner wall on which an intermetallic compound catalytic layer is provided. This catalytic layer has the following technical effects: During the melting of the cored wire, the intermetallic compound layer can serve as a catalyst or heterogeneous nucleation substrate for the dissolution and dispersion of the inoculant alloy powder in the molten iron. This reduces the interfacial energy barrier for the inoculant elements to integrate into the molten iron, accelerates the dissolution rate of the powder, and promotes its uniform distribution in the molten iron, thereby improving the utilization rate of effective elements in the inoculant.
[0009] Preferably, the core-shell structured composite particle specifically includes: A core composed of a mixture of barium and calcium powder; And a shell made of a mixture of silicon powder and rare earth powder that covers the outside of the core.
[0010] By placing highly reactive barium and calcium in the core, and physically protecting them with an outer shell composed of silicon and rare earth elements, the risk of oxidation during production and storage is reduced.
[0011] Preferably, the intermetallic compound catalyst layer is composed of a compound of iron and silicon or a compound of iron and rare earth elements, and the thickness of the catalyst layer is 5-50 micrometers.
[0012] This thickness range ensures that the layer provides effective catalysis without significantly affecting the overall composition of the cored wire.
[0013] Preferably, the rare earth element is lanthanum or cerium.
[0014] These two elements play a role in purifying molten iron, neutralizing harmful elements, and improving the morphology of graphite in cast iron.
[0015] Preferably, the steel wire carrier is rolled from a low-carbon steel strip with a thickness of 0.3-0.5 mm. This specification of steel strip has sufficient strength and flexibility, and is suitable for the industrial production of cored wire.
[0016] A second aspect of the present invention provides a method for preparing inoculated cored wire for cast iron, the method comprising the following steps: S1. Preparation of composite inoculated alloy powder with core and shell structure; S2. The inner wall of the steel wire carrier is activated to form an intermetallic compound catalytic layer; S3. Under an inert gas protective environment, the composite inoculated alloy powder is filled into the steel wire carrier and then closed and compacted. S4. Finish, inspect and package the formed cored wire.
[0017] Preferably, step S1, namely the step of preparing composite inoculated alloy powder with a core and shell structure, specifically includes: A fluidized bed coating process is used to coat the surface of a core material composed of barium and calcium powder with a shell material composed of silicon and rare earth powder at a temperature of 200-350℃ and in an inert atmosphere.
[0018] This process can form uniform and structurally complete composite particles under controlled conditions.
[0019] Preferably, step S2, which is the step of activating the inner wall of the steel wire carrier to form an intermetallic compound catalyst layer, specifically includes: Vacuum magnetron sputtering was employed at a vacuum level of 5.0 × 10⁻⁶. -4 Up to 9.0×10 -4 Under the condition of Pa, the intermetallic compound catalyst layer is deposited on the inner wall of the steel wire carrier using a sputtering power of 2-5 kW.
[0020] This method can produce thin film layers with uniform thickness and strong adhesion to the substrate.
[0021] Preferably, the inert gas protective environment in step S3 has an oxygen content of less than 10 ppm and a dew point temperature of less than -60°C.
[0022] Filling and closing under these conditions can minimize the risk of oxidation and failure of the active components in the inoculated alloy powder during manufacturing.
[0023] The closing compaction is accomplished by applying a pressure of 80-120 kN to ensure the physical sealing of the cored wire.
[0024] Preferably, step S4, which is the step of finishing, inspecting and packaging the formed cored wire, specifically includes: using online eddy current testing and laser diameter measurement to perform quality inspection on the formed cored wire to ensure product continuity and dimensional consistency; The cored wire is then sealed with a vacuum sealing film to ensure its quality stability during transportation and storage.
[0025] This invention provides a cored wire for cast iron. It has the following advantages: 1. This invention achieves the time-sequential release of inoculating elements by using highly active barium and calcium powders as the core and covering them with silicon and rare earth powders to form a protective outer shell. This results in a long-lasting and stable inoculation effect and achieves the technical effect of inhibiting inoculation decline. Compared with the existing technology that simply mixes various powders mechanically, this invention solves the problems of premature concentrated reaction of active components and rapid decline of inoculation effect over time.
[0026] 2. The present invention pre-embeds an intermetallic compound catalytic layer on the inner wall of the steel wire carrier. This design, together with the optimized barium-calcium-rare earth composite component inside, significantly improves the melting and dispersion efficiency of the inoculant powder and the utilization rate of effective elements. Compared with the traditional method of using an inert steel strip to wrap a simple inoculant, the present invention solves the problem that some powders fail due to poor melting or being wrapped by the molten steel strip, resulting in low inoculation efficiency and unstable batch performance.
[0027] 3. The core and shell particle structure adopted in this invention, combined with the manufacturing process of full-process inert atmosphere protection, fundamentally isolates the highly active inoculum components from air, ensuring the chemical stability of the product during production and storage. Compared with the existing technology solutions where production and storage conditions are not strictly controlled, this invention solves the defects of its active elements being easily oxidized and degraded, resulting in large performance fluctuations and poor reliability between product batches. Attached Figure Description
[0028] Figure 1 This is a schematic diagram of the preparation method of the present invention. Detailed Implementation
[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0030] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available products or can be prepared by known methods.
[0031] Please see the appendix Figure 1 : Example 1 Component ratio: The composition of the inoculated alloy powder used in this embodiment, by weight, is as follows: 70 parts silicon powder, 15 parts barium powder, 10 parts calcium powder, 0.5 parts lanthanum powder, with the remainder being iron and impurities.
[0032] Preparation steps: 1. Preparation of composite inoculated alloy powder: 15 parts barium powder and 10 parts calcium powder were mixed evenly to form the core material. Using a fluidized bed coating process, under an argon atmosphere at a temperature of 275℃, a shell material composed of 70 parts silicon powder and 0.5 parts lanthanum powder was uniformly coated on the surface of the fluidized core material to obtain a composite inoculated alloy powder with a core-shell structure.
[0033] 2. Preparation of catalytic steel wire support: A 0.4 mm thick low-carbon steel strip was selected as the substrate. Vacuum magnetron sputtering was employed at a vacuum level of 7.0 × 10⁻⁶. -4 Under conditions of Pa and sputtering power of 3.5 kW, an iron-silicon compound film was deposited on one side of the steel strip to form an intermetallic compound catalyst layer with a thickness of 25 micrometers, thereby obtaining an activated steel wire carrier.
[0034] 3. Manufacturing of cored wire assemblies: Under nitrogen protection, with an oxygen content below 10 ppm and a dew point temperature below -60°C, the activated steel wire carrier prepared in step 2 is rolled into a U-shaped groove, and the composite inoculated alloy powder prepared in step 1 is filled into it. Subsequently, the U-shaped groove steel strip is closed and compacted at a compaction pressure of 100 kN to form a cored wire.
[0035] 4. Finishing and Packaging: The formed cored wires are subjected to online eddy current testing and laser diameter measurement. After passing the test, they are coiled and sealed with vacuum sealing film.
[0036] Example 2 Component ratio: The composition of the inoculated alloy powder used in this embodiment is as follows by weight: 65 parts silicon powder, 12 parts barium powder, 8 parts calcium powder, 0.1 parts cerium powder, with the remainder being iron and impurities.
[0037] Preparation steps: 1. Preparation of composite inoculated alloy powder: 12 parts barium powder and 8 parts calcium powder were mixed evenly to form the core material. A fluidized bed coating process was used to coat the surface of the core material with a shell material composed of 65 parts silicon powder and 0.1 parts cerium powder under an inert atmosphere at a temperature of 200°C, thus obtaining a composite inoculated alloy powder.
[0038] 2. Preparation of catalytic steel wire support: A 0.3 mm thick low-carbon steel strip was selected as the substrate. Vacuum magnetron sputtering was employed at a vacuum level of 5.0 × 10⁻⁶. -4 Under conditions of Pa and sputtering power of 2 kW, an iron-rare earth compound film was deposited on one side of the steel strip to form an intermetallic compound catalyst layer with a thickness of 5 micrometers, thereby obtaining an activated steel wire carrier.
[0039] 3. Manufacturing of cored wire assemblies: Under an inert gas protective environment, the activated steel wire carrier prepared in step 2 is rolled into a U-shaped groove, and the composite inoculated alloy powder prepared in step 1 is filled into it. Subsequently, the U-shaped groove steel strip is closed and compacted at a compaction pressure of 80 kN to form a cored wire.
[0040] 4. Finishing and Packaging: The formed cored wires are subjected to quality inspection. After passing the inspection, they are coiled and sealed with vacuum plastic film.
[0041] Example 3 Component ratio: The composition of the inoculated alloy powder used in this embodiment, by weight, is as follows: 75 parts silicon powder, 18 parts barium powder, 12 parts calcium powder, 1.0 part lanthanum powder, with the remainder being iron and impurities.
[0042] Preparation steps: 1. Preparation of composite inoculated alloy powder: 18 parts of barium powder and 12 parts of calcium powder were mixed evenly to form the core material. A fluidized bed coating process was used to coat the surface of the core material with a shell material composed of 75 parts of silicon powder and 1.0 part of lanthanum powder under an inert atmosphere at 350℃, thus obtaining a composite inoculated alloy powder.
[0043] 2. Preparation of catalytic steel wire support: A 0.5 mm thick low-carbon steel strip was selected as the substrate. Vacuum magnetron sputtering was employed at a vacuum level of 9.0 × 10⁻⁶. -4 Under conditions of Pa and sputtering power of 5 kW, an iron-silicon compound film was deposited on one side of the steel strip to form an intermetallic compound catalyst layer with a thickness of 50 micrometers, thereby obtaining an activated steel wire carrier.
[0044] 3. Manufacturing of cored wire assemblies: Under an inert gas protective environment, the activated steel wire carrier prepared in step 2 is rolled into a U-shaped groove, and the composite inoculated alloy powder prepared in step 1 is filled into it. Subsequently, the U-shaped groove steel strip is closed and compacted at a compaction pressure of 120 kN to form a cored wire.
[0045] 4. Finishing and Packaging: The formed cored wires are subjected to quality inspection. After passing the inspection, they are coiled and sealed with vacuum plastic film.
[0046] Comparative Example 1: Compared with Example 1, the difference is that the amount of barium powder used in the inoculated alloy powder composition is 10 parts, while the rest are the same.
[0047] Comparative Example 2: Compared with Example 1, the difference is that the amount of silicon powder used in the inoculated alloy powder composition is 80 parts, while the rest are the same.
[0048] Comparative Example 3: Compared with Example 1, the difference is that its inoculated alloy powder composition does not contain rare earth lanthanum powder, while the rest are the same.
[0049] Comparative Example 4: Compared with Example 1, the difference is that the inoculated alloy powder component does not contain barium powder, and 15 parts by weight are replaced by calcium powder, that is, the total amount of calcium powder is 25 parts, and the rest are the same.
[0050] Comparative Example 5: Compared with Example 1, the difference is that in its preparation step 1, the fluidized bed coating process is not used to prepare core-shell structured particles. Instead, all component powders (silicon, barium, calcium, lanthanum) are directly mechanically mixed in a V-type mixer to obtain homogeneous mixed inoculated powder. All other aspects are the same.
[0051] Comparative Example 6: Compared with Example 1, the difference is that in its preparation step 2, the activation treatment of the inner wall of the low carbon steel strip by vacuum magnetron sputtering is omitted, that is, the inner wall of the steel wire carrier used does not have an intermetallic compound catalyst layer, and the rest are the same.
[0052] Experiment 1: Experimental objective: This study verifies the effectiveness and superiority of the weight range of core elements (such as barium and silicon) in the inoculated alloy composition defined in this invention on the final mechanical properties of cast iron.
[0053] Experimental group: Samples of inoculated cored wire prepared in Example 1; Comparative Example 1: Inoculated cored wire sample prepared; Comparative Example 2: Inoculated wire sample prepared.
[0054] Experimental steps: 1. Iron smelting and composition adjustment: A batch of gray cast iron conforming to the HT250 standard was smelted using a medium-frequency induction furnace. After the molten iron was completely melted, the temperature was raised to 1480℃-1520℃. Samples were taken to analyze the chemical composition of the molten iron, and fine adjustments were made using carburizing agents and ferrosilicon to ensure that the baseline composition of each key element (C, Si, Mn, P, S) was consistent.
[0055] 2. Pregnancy treatment: The batch of molten iron was divided into three equal portions and poured into three separate, preheated ladles. Using a cored wire feeder, cored wire samples from Example 1, Comparative Example 1, and Comparative Example 2 were fed into the three ladles at the same feeding speed and at an addition rate of 1.5 kg / ton per unit weight of molten iron.
[0056] 3. Sample casting: After the inoculation treatment is completed, the mixture is allowed to stand for 1 minute, and then molten iron at a temperature range of 1380℃-1420℃ is poured into pre-made tensile test specimen sand molds conforming to GB / T 228.1. Six tensile specimens are cast for each group.
[0057] 4. Performance Testing: After the samples had completely cooled, they were cleaned of sand and polished. Using a universal testing machine, room temperature tensile tests were performed on the samples of each group, and their tensile strength (MPa) and elongation after fracture (%) were recorded. Outliers were removed, and the average value of each group's performance was calculated (experimental data are shown in Table 1).
[0058] Table 1: Test Results of the Influence of Inoculated Alloy Composition Ratio on the Mechanical Properties of Cast Iron From Table 1, we can obtain: As shown in Table 1, the cast iron specimens treated with the sample from Example 1 exhibited significantly higher tensile strength and elongation after fracture than those from Comparative Example 1 and Comparative Example 2. This result directly confirms the effectiveness of the component ratio range defined in this invention.
[0059] The performance degradation in Comparative Example 1 is fundamentally due to insufficient barium content. Barium, as a potent and long-lasting inoculant, works by forming complex oxides or sulfur oxides with high melting points and low solubility in molten iron, serving as a heterogeneous nucleation substrate. When the barium content is below 12 parts, the number of effective nucleation sites is insufficient, leading to increased supercooling of graphite crystallization and a greater tendency to form coarse D-type and E-type graphite morphologies. These large and unevenly distributed graphite flakes cause severe tearing effects on the matrix, becoming stress concentration sources and significantly deteriorating the material's strength and toughness.
[0060] Comparative Example 2 exhibited the worst performance, its problem stemming from excessive silicon content. While silicon is a key element promoting graphitization, exceeding the upper limit of 75 parts per unit area has negative effects. Excessive silicon strongly promotes ferrite formation, excessively weakening the proportion and quality of the pearlite matrix. Ferrite is a relatively weak phase, directly leading to a decrease in the overall tensile strength of the material. Simultaneously, excessive silicon disrupts the synergistic balance with other active elements such as barium and calcium, failing to create an optimal inoculation environment. Consequently, its overall inoculation effect is inferior to the balanced formulation. The component range defined in this invention precisely ensures a precise balance between strong inoculation and a robust matrix.
[0061] Experiment 2: Experimental objective: This invention verifies the synergistic technical effect between rare earth elements and core inoculating elements such as barium and calcium in the inoculated alloy composition defined in this invention, and their importance to the comprehensive mechanical properties of cast iron.
[0062] Experimental group: Samples of inoculated cored wire prepared in Example 1; Comparative Example 3: Inoculated cored wire sample prepared; Comparative Example 4: Inoculated wire sample prepared.
[0063] Experimental steps: 1. Iron smelting and composition adjustment: A batch of gray cast iron conforming to the HT250 standard was smelted using a medium-frequency induction furnace. After the molten iron was completely melted, the temperature was raised to 1480℃-1520℃. Samples were taken to analyze the chemical composition of the molten iron to ensure that the baseline composition of each key element was consistent.
[0064] 2. Pregnancy treatment: The batch of molten iron was divided into three equal portions and poured into three separate, preheated ladles. Using a cored wire feeder, cored wire samples from Example 1, Comparative Example 3, and Comparative Example 4 were fed into the three ladles at the same feeding speed and at an addition rate of 1.5 kg / ton per unit weight of molten iron.
[0065] 3. Sample casting: After the inoculation treatment is completed, let it stand for 1 minute, and then pour molten iron in the temperature range of 1380℃-1420℃ into pre-made tensile test sand molds conforming to GB / T 228.1 standard and V-notch impact test sand molds conforming to GB / T 229 standard.
[0066] 4. Performance Testing: After the samples have completely cooled, they are cleaned of sand and polished. The tensile strength (MPa) of the tensile samples is tested using a universal testing machine. The Charpy impact toughness (J) of the impact samples is tested using a pendulum impact testing machine. The average value of each set of properties is calculated (experimental data are shown in Table 2).
[0067] Table 2: Test results of the synergistic effect of inoculated alloy components on the comprehensive properties of cast iron Group Mean tensile strength (MPa) Charpy impact toughness mean (J) Remark Example 1 261.4 5.8 Complete composition Comparative Example 3 243.9 4.3 Free of rare earth elements Comparative Example 4 228.5 3.6 Barium is not present; it is replaced by calcium. From Table 2, we can obtain: The experimental results clearly show that, compared with Example 1, Comparative Examples 3 and 4, which lacked any key synergistic component, exhibited a significant decrease in the tensile strength and impact toughness of the treated cast iron. This demonstrates the indispensable synergistic effect among the components in the formulation of this invention.
[0068] The performance degradation of Comparative Example 3 is directly attributed to the lack of rare earth elements. Rare earth elements play a dual key role in the formulation of this invention. First, as a strong deoxidizing and desulfurizing agent, it can purify molten iron, removing or neutralizing harmful impurities such as sulfur and oxygen, providing a cleaner metallurgical environment for subsequent graphite nucleation. Second, rare earth elements can adsorb onto the interface of graphite crystal growth, altering its growth habit and making the lamellar ends of type A graphite more passivated. This significantly reduces the cutting effect of graphite flakes on the metal matrix and the degree of stress concentration, thereby effectively improving the toughness of the material.
[0069] The further decline in performance in Comparative Example 4 reveals a synergistic relationship of functional complementarity between barium and calcium, rather than a simple substitutability relationship. Although calcium and barium are both alkaline earth metal inoculating elements, their mechanisms of action and effects differ. Calcium is highly reactive, reacting rapidly in the early stages of inoculation to provide a large number of nucleation sites, but its products have poor stability in high-temperature molten iron, resulting in rapid decline in inoculation effectiveness. Barium, on the other hand, can form complex sulfur oxides or silicate particles with higher melting points and more stable structures, serving as a more long-lasting nucleation substrate and effectively inhibiting inoculation decline. The solution of this invention utilizes the combination of calcium's "instantaneous high efficiency" and barium's "stable long-lasting effect" to achieve full-time coverage of the inoculation process. In Comparative Example 4, only calcium was used to replace barium, disrupting this mechanism of combining long-term and short-term effects, leading to insufficient persistence of the inoculation effect and ultimately manifesting as a significant reduction in overall mechanical properties.
[0070] Experiment 3: Experimental objective: The effects of the "core-shell structure" in this invention on inhibiting incubation decline and the effects of the "inner wall catalytic layer" on improving incubation efficiency were verified respectively.
[0071] Experimental group: Samples of inoculated cored wire prepared in Example 1; Comparative Example 5: Inoculated cored wire sample prepared; Comparative Example 6: Inoculated wire sample prepared.
[0072] Experimental steps: 1. Iron smelting and grouping: A batch of gray cast iron conforming to the HT250 standard was smelted using a medium-frequency induction furnace. After the molten iron was completely melted, the temperature was raised to 1480℃-1520℃, and samples were taken for analysis to ensure that the reference composition was consistent. The molten iron was divided into three equal portions and poured into three separate, preheated ladles.
[0073] 2. Pregnancy treatment: Using a cored wire feeder, cored wire samples from Example 1, Comparative Example 5, and Comparative Example 6 were fed into three ladles at the same feeding speed and with an addition rate of 1.5 kg / ton per unit weight of molten iron.
[0074] 3. Time-sampling and pouring: After the incubation treatment of each ladle was completed, samples were taken and poured at two different time points: Immediate sampling: Within 1 minute after treatment, immediately pour the first batch of tensile specimens conforming to GB / T 228.1 standard.
[0075] Delayed sampling: After the ladle is left to stand in the heat preservation furnace for 10 minutes, the second batch of tensile test specimens is poured again.
[0076] 4. Performance Testing: After all samples have completely cooled, they are cleaned and polished. Using a universal testing machine, room temperature tensile tests are performed on the samples of each group at each time point, and the average tensile strength (MPa) is recorded and calculated (experimental data are shown in Table 3).
[0077] Table 3: Test Results on the Impact of Cored Wire Structural Innovation on Inoculation Effect From Table 3, we can obtain: Experimental data show that the sample of Example 1 exhibits the best performance in both immediate incubation effect and anti-deterioration performance, which intuitively proves the synergistic effect of the two structural innovations in this invention.
[0078] Comparing the results of Example 1 and Comparative Example 5, the key role of the core-shell structure in suppressing inoculation decay is confirmed. Comparative Example 5 used a simple mechanical mixing of powders, where all active components melted simultaneously upon contact with molten iron. Although this produced a considerable immediate effect, the highly reactive barium and calcium elements were also rapidly oxidized or aggregated and became ineffective, leading to a sharp decline in the inoculation effect within 10 minutes. In contrast, the core-shell structure of this invention achieves the "sequential release" of inoculating elements. The outer silicon shell melts first to provide basic inoculation and protect the core; subsequently, the barium and calcium elements in the core are slowly released, continuously replenishing the molten iron with fresh, diffuse nucleation nuclei, thereby compensating for natural decay and maintaining the inoculation effect at a high level for a longer period.
[0079] Comparing the instantaneous tensile strength data of Example 1 and Comparative Example 6, the synergistic effect of the inner wall catalyst layer is obvious. Comparative Example 6 uses a traditional inert steel strip, where some inoculant powder is easily encapsulated by the molten iron in the steel strip or captured by slag during the melting process, resulting in a reduced actual effective utilization rate. The intermetallic compound catalyst layer designed in this invention essentially introduces a highly efficient "interfacial medium" between the inoculant and the molten iron. This catalyst layer has a lower melting point and better affinity, which can significantly reduce the interfacial energy barrier for the inoculant powder to integrate into the molten iron, promote rapid and uniform dispersion of the powder, and avoid agglomeration and loss. This allows more active elements to participate in the inoculation reaction with the same amount added, thereby obtaining higher inoculation efficiency and better final mechanical properties.
[0080] The embodiments described in this specific implementation are preferred embodiments of this application and are not intended to limit the scope of protection of this application. Identical components are represented by the same reference numerals. Therefore, all equivalent changes made to the structure, shape, and principle of this application should be covered within the scope of protection of this application.
Claims
1. A type of inoculated cored wire for cast iron, characterized in that, The steel wire carrier is filled with inoculant alloy powder, which comprises the following components by weight: Silicon powder 65-75 parts; Barium powder 12-18 parts; Calcium powder 8-12 parts; Rare earth 0.1-1.0 parts; The balance is iron and impurities; The inoculant alloy powder is a composite particle with core-shell structure; The steel wire carrier has an inner wall, on which an intermetallic compound catalytic layer is provided.
2. The inoculation cored wire for cast iron according to claim 1, characterized by The composite particle with core-shell structure comprises: The core is composed of a mixture of barium and calcium powders; The shell is composed of a mixture of silicon and rare earth powders coated on the outside of the core.
3. The inoculation cored wire for cast iron according to claim 1, characterized by The intermetallic compound catalytic layer is composed of iron and silicon compounds or iron and rare earth compounds, and has a thickness of 5-50 microns.
4. The inoculation cored wire for cast iron according to claim 1, characterized by The rare earth is lanthanum or cerium.
5. The inoculation cored wire for cast iron according to claim 1, characterized by The steel wire carrier is rolled from low-carbon steel strip with a thickness of 0.3-0.5 mm.
6. A method for producing the inoculation cored wire for cast iron as claimed in any one of claims 1 to 5, characterized by, The method comprises the following steps: S1, preparing a composite inoculant alloy powder with core-shell structure; S2, activating the inner wall of the steel wire carrier to form an intermetallic compound catalytic layer; S3, filling the composite inoculant alloy powder into the steel wire carrier under inert gas protection environment, and performing closed compaction; S4, finishing, testing and packaging the formed cored wire.
7. A method of producing an inoculation cored wire for cast iron according to claim 6, characterized in that, The step of preparing a composite inoculant alloy powder with core-shell structure comprises: Using fluidized bed coating process, the shell material composed of silicon and rare earth powders is coated on the surface of the core material composed of barium and calcium powders at a temperature of 200-350℃ and in an inert atmosphere.
8. A method of producing an inoculation cored wire for cast iron according to claim 6, characterized by, The step of activating the inner wall of the steel wire carrier to form an intermetallic compound catalytic layer comprises: The intermetallic compound catalytic layer is formed by vacuum magnetron sputtering process on the inner wall of the steel wire carrier under the condition of vacuum degree of 5.0×10 -4 to 9.0×10 -4 Pa, and sputtering power of 2-5 kW.
9. The method of producing an inoculation cored wire for cast iron according to claim 6, characterized by, The oxygen content of the inert gas protection environment is less than 10 ppm, and the dew point temperature is less than -60℃; The closed compaction is completed by applying a pressure of 80-120 kN.
10. The method of producing an inoculation cored wire for cast iron according to claim 6, characterized by, The step of finishing, testing and packaging the formed cored wire comprises: Using online eddy current flaw detection and laser diameter measurement to test the quality of the formed cored wire; Using vacuum plastic film to finally seal and package the coiled cored wire.